Evolutionary Origin of the Interferon–Immune Metabolic Axis: The Sterol–Vitamin D Link - Newmark, Harry; Dantoft, Widad; Ghazal, Peter (Frontiers in Immunology, 2017)
In vertebrate animals the sterol metabolic network is emerging as a central player in immunity and inflammation. Upon infection, flux in the network is acutely moderated by the interferon response through direct molecular and bi-directional communications. How sterol metabolism became linked to interferon control and for what purpose is not obvious. Here we deliberate on the origins of these connections based on a systematic review of the literature. A narrative synthesis of publications that met eligibility criteria allowed us to trace an evolutionary path and functional connections between cholesterol metabolism and immunity. The synthesis supports an ancestral link between toxic levels of cholesterol-like products and the vitamin D receptor (VDR). VDR is an ancient nuclear hormone receptor that was originally involved in the recognition and detoxification of xenobiotic marine biotoxins exhibiting planar sterol ring scaffolds present in aquatic environments. Co-adaptation of this receptor with the acquisition of sterol biosynthesis and interferons in vertebrate animals set a stage for re-purposing and linking a pre-existing host protection mechanism of harmful xenobiotics to become an important regulator in three key interlinked biological processes; bone development, immunity and calcium homeostasis. We put forward the hypothesis that sterol metabolites, especially oxysterols, have acted as evolutionary drivers in immunity and may represent the first example of small-molecule metabolites linked to the adaptive co-evolution and diversification of host metabolic and immune regulatory pathways.